Dynamics Contact Analysis of the Slewing Reducer Rigid-flexible Coupled based on ABAQUS - Lu Chao; Chen Jie; Hong Rongjing (Jixie chuandong, 2015)
The slewing reducer is widely applied in the field of solar photovoltaic power generation.Aiming at the high probability problem of the contact fatigue strength at the gear surface in all fatigue failure,by using the ABAQUS,the simulation analysis of dynamics contact problem is carried out.In order to simplify the problem and improve the precision of the model,a novel method is proposed.The worm is taken as a rigid body,and the slewing gear is taken as the flexible body,and then the contact fatigue analysis is carried out.The simulation results show that the model tallies with the actual situation,and the analysis results can provide guidance for the design optimization.